QKI-induced circ_0001766 inhibits colorectal cancer progression and rapamycin resistance by miR-1203/PPP1R3C/mTOR/Myc axis - Yulai Zhou; Yan Gao; Yinghui Peng; Changjing Cai; Ying Han; Yihong Chen; Gongping Deng; Yanhong Ouyang; Hong Shen; Shan Zeng; Yangfeng Du; Zemin Xiao (Cell Death Discovery)
Abstract Colorectal cancer (CRC) is the third most common cancer and remains a significant challenge due to high rates of drug resistance and limited therapeutic options. Circular RNAs (circRNAs) are increasingly recognized for their roles in CRC initiation, progression, and drug resistance. However, no circRNA-based therapies have yet entered clinical development, underscoring the need for comprehensive detection and mechanistic studies of circRNAs in CRC. Here, we identified and characterized a circular RNA, circ_0001766 (hsa_circ_0001766), through microarray analysis of CRC tissues. Our results showed that circ_0001766 is downregulated in CRC tissues and closely associated with patient survival and metastasis. Functional experiments demonstrated that circ_0001766 inhibits CRC cell proliferation, migration and invasion both in-vitro and in-vivo. Mechanistically, hypoxia downregulates Quaking (QKI), an RNA-binding protein essential for the biogenesis of circ_0001766 by binding to introns 1 and 3 of PDIA4 pre-mRNA. Reduced QKI expression under hypoxic conditions leads to decreased circ_0001766 levels in CRC. Circ_0001766 acts as a competitive endogenous RNA, sponging miR-1203 to prevent the degradation of PPP1R3C mRNA. Loss of circ_0001766 results in decreased PPP1R3C expression, leading to the activation of mTOR signaling and increased phosphorylation of Myc, which promotes CRC progression and rapamycin resistance. Our study reveals that overexpression of circ_0001766 or PPP1R3C in CRC cells inhibits the mTOR and Myc pathway, thereby resensitizing cells to rapamycin. The combination of circ_0001766 or PPP1R3C with rapamycin markedly inhibits CRC cell proliferation and induces apoptosis by reducing rapamycin-induced Myc phosphorylation. In summary, our study elucidates a critical circ_0001766/miR-1203/PPP1R3C axis that modulates CRC progression and rapamycin resistance. Our findings highlight circ_0001766 as a promising therapeutic target in CRC, providing a new avenue for enhancing the efficacy of existing treatments and overcoming drug resistance.